(untitled) (World Bulletin of Management and Law, 2024)
The article provides a scientific-theoretical analysis of the content of the medical service contract, the concept of a medical service contract, the concepts of medical care, medical services, the legal nature and subject of these contracts, and describes the results of the study on the issue of the form of the medical service contract within the framework of this relationship.